Pembimbingan Usaha Beternak Unggas dan Pengolahan Limbah Peternakan Unggas Pada Masyarakat di Desa Wakan Kecamatan Jerowaru Lombok Timur - Dwi Kusuma Permatasari; Syamsuhaidi Syamsuhaidi; Erwan Erwan; Wiryawan Wiryawan; Sumiati Sumiati; Tapaul Rozy (Jurnal Gema Ngabdi, 2020)
This dedication activity was based on requests from the management of the Ar-Rusydiny Segaet Islamic boarding school and the people of Wakan village, Jerowaru sub-district, East Lombok regency to get guidance on poultry raising and processing of poultry manure waste, which is one of the activities in the boarding school. The activity involved the community and students of Islamic boarding schools in the village of Wakan. Activities include counseling on poultry farming and poultry farm waste processing in the form of hongkong caterpillar cultivation using poultry droppings. The method used is a participatory method, counseling, and waste treatment practices with various alternative treatment processes. The target to be achieved from this activity is the community and boarding school students motivated to conduct poultry farming and poultry farm waste processing business, and make it one of the leading programs in boarding schools. Based on the results of the community service activities, various problems were found, namely the ignorance of the community in processing poultry, cow, and goat manure waste which is often complained of by the community. The Wakan village community and the management of the Ar-Rusydiny Segaet boarding school do not know how to handle livestock waste. Wakan villagers enthusiastically participated in counseling and practices of sewage treatment, as evidenced by the number of participants who took part, 37 people and during the active discussion session, as well as the emergence of community commitment to process waste into useful products.